(untitled) (Periphērica, 2020)
Although transnationality as a phenomenon is as old as film, the contemporary reflection on this topic and the plurality of approaches that converge on it have opened new lines of analysis to evaluate the impact that this reality exerts on the film industry. My intention in this study is to propose a typology that reflects the impact of transnationality in the specific case of Spanish film to explore the dynamics that control our cinematic production in the third millennium. I propose six segments to structure my approach to the Spanish film industry: 1. Production modes; 2. Transnational subjects; 3. Aesthetic registers; 4. Themes; 5. Ethics and ideology; 6. Critical and moviegoer reception. Within this framework, I will explore the dialectics between the national essence of Spanish film and its transnationality, the impact of different financial models, the multidirectional movements of our actors and directors, esthetic influences, the ethics of the industry and the response of critics and viewers to a film industry that swings between preserving and erasing its identity markers.